2021
DOI: 10.1016/j.shaw.2021.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Problems and Lifestyle Changes Among Novice Working-From-Home Workers Amid the COVID-19 Pandemic

Abstract: Background Social distancing by working-from-home is an effective measure to decrease the spread of COVID-19. However, this new work pattern could also affect the well-being of workers. Therefore, the aim of the study was to study the magnitude of occupational health problems and lifestyle changes among workers who have only recently started working from home. Methods A cross-sectional study was conducted using online self-administered questionnaires during the coronavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 23 publications
1
77
1
8
Order By: Relevance
“…In a survey conducted more than six months after the COVID-19 pandemic outbreak and including 194 employees who switched to working from home because of the pandemic, Guler et al found that almost half of the study population (46.9%) reported an increase in body weight during the working-from-home period [51]. Another survey, including 869 individuals working from home during the COVID-19 pandemic, reported a 41% prevalence of weight gain, with a dose-response relationship with the intensity of working from home as the number of days per week spent working from home [52]. Of note, a significant association between sedentary work (measured as sitting time) and higher body mass index was already reported in scientific literature [53].…”
Section: Working From Home and Cardiometabolic Diseasementioning
confidence: 99%
“…In a survey conducted more than six months after the COVID-19 pandemic outbreak and including 194 employees who switched to working from home because of the pandemic, Guler et al found that almost half of the study population (46.9%) reported an increase in body weight during the working-from-home period [51]. Another survey, including 869 individuals working from home during the COVID-19 pandemic, reported a 41% prevalence of weight gain, with a dose-response relationship with the intensity of working from home as the number of days per week spent working from home [52]. Of note, a significant association between sedentary work (measured as sitting time) and higher body mass index was already reported in scientific literature [53].…”
Section: Working From Home and Cardiometabolic Diseasementioning
confidence: 99%
“…Almost one half (47%) of the participants in the total sample reported some weight gain consisting with the results of a study conducted in Bangkok which showed that 41% of workers who shifted to work from home reported weight gain. 13 This finding is alarming and might result in complications of existing chronic diseases and can contribute to the development of new ones. There was a significant difference between the WFH group, and the working regularly group in terms of weight gain, where unsurprisingly greater weight gain was reported among the WFH group.…”
Section: Discussionmentioning
confidence: 99%
“…Of those who shifted to WFH, 39% reported eating larger quantities of food, 33% reduction in daily physical activity, 41% weight gain, and 21% reported insomnia. 13 Decreased walking among those worked from home during the pandemic was observed in another study and was linked to depression. 14 To our knowledge, only few studies have assessed the impact of working from home on lifestyle aspects during COVID-19.…”
mentioning
confidence: 84%
“…Occupational health is defined as one of the public health branches that aim to reduce the health deviations of employees during their work (Selem et al, 2019). Moreover, Ekpanyaskul and Padungtod (2021) and Zhang et al ( 2020) affirmed that occupational health has precise measures that help to magnify the employees' health and prepare them physically if applied effectively in proportion to their work nature. The awareness tips should provide…”
Section: Occupational Health Measuresmentioning
confidence: 99%